Cardiovascular Disease and Depression/Anxiety, Two Complication of Menopause Status - Susan, Darroudi; Maryam, Saberi-Karimian; Fatemeh, Sadabadi; Maryam, Tayefi; Batool, Tayefi; Zahra, Asadi; Toktam, Sahranavard; Sajjad, Sabour; Farnoush, Kermanshahi; Effat, Bahadory; Gordon, A. Ferns; Habibollah, Esmaily; et al. (International Journal of Nutrition, 2019)
Objective Postmenopausal women are at an increased risk of Cardiovascular Disease. We aimed to investigate whether this risk differed between individuals with a naturally occurring and other reasons for menopause within a large population-based Iranian sample. Study Design A total number of 1763 postmenopausal women (defined by amenorrhea for more than a year, or FSH > 30-40 mIU/ml), 900 of them with a natural menopause and 863 of them with other reasons for menopause caused by (hysterectomy without oophorectomy or one side oophorectomy, hysterectomy with oophorectomy or two side oophorectomy without hysterectomy) were recruited as part of the Mashhad Stroke and Heart Atherosclerotic Disorders (MASHAD) cohort study. Biochemical and hematological risk factors were measured in all the subjects and the data were analyzed by SPSS software version 20 Results There was a significant difference in the presence of cardiovascular disease in the natural menopause group compared with other reasons for menopause group (p<0.05). There was also a meaningful difference between the prevalence of depression and anxiety in the natural menopause individuals compared with other reasons for menopause group (p<0.05). Discussion High prevalence of CVD, depression and anxiety in other reasons in menopause women were observed among Mashhad urban females. It should be considered as a noticeable message. Furthermore, studies are necessary to determine different parameters between evaluating CVD, depression and anxiety among menopauses women.
Keywords: Postmenopausal; Depression; Anxiety; Cardiovascular Disease.